Effects of biochar and crop residues application on chemical properties of a degraded soil of South Malang, and P uptake by maize - B D Satriawan; E Handayanto (Brawijaya University, 2015)
Low productivity of food crops on marginal dry lands of South Malang, East Java occurs due to low levels of soil fertility in the region due to low soil organic matter content and low content of available P. The purpose of this study was to evaluate the effect of the combination of biochar and plant litter on chemical properties of a degraded soil of South Malang, and P uptake by maize. The treatments tested in this study was a combination of types of biochar (sugarcane litter biochar and maize litter biochar), and the type of fresh litter (sugarcane and maize). Biochar doses applied were 0, 20 and 40 t biochar / ha, whereas the doses of fresh litters applied were 0, 40, and 80 t litter / ha. Three maize seed of BISI 2 variety was grown in each pot (treatment) for 49 days. Nine treatments were arranged in a completely randomized design with three replications. The results showed that application of litter and biochar tended to lower pH, CEC, exchangeable Ca, and total P the soil studied. The interaction of litter and biochar did not significantly increase P availability in the soil. However, application of litter and biochar also increased P uptake by maize. The best treatment for maximum increase of P availability and uptake of P was application 80 t sugarcane fresh litter / ha and 40 t maize litter biochar / ha.